Challenges of qualitative data sharing in social sciences - Tanja Vuckovic Juros (European Science Editing)
Open science offers hope for new accountability and transparency in social sciences. Nevertheless, it still fails to fully consider the complexities of qualitative research, as exemplified by a reflection on sensitive qualitative data sharing. As a result, the developing patterns of rewards and sanctions promoting open science raise concern that quantitative research, whose “replication crisis” brought the open science movement to life, will benefit from “good science” re-evaluations at the expense of other research epistemologies, despite the necessity to define accountability and transparency in social sciences more widely and not to conflate those with either reproducibility or data sharing.